Australian Clinical Legal Education: Designing and Operating a Best Practice Clinical Program in an Australian Law School by Adrian Evans, Anna Cody, Anna Copeland, Jeff Giddings, Peter Joy, Mary Anne Noone and Simon Rice - Francina Cantatore
Introduction: The book provides a fresh look at Clinical Legal Education (CLE) in Australia in 2017, and examines the diverse factors which influence law clinics during a time when many disruptions are occurring in higher education. The authors argue that clinics make numerous contributions to Australian legal education, including fostering student awareness of concepts of justice and how the law and legal processes impact on people. They express the view that CLE can challenge a contemporary overemphasis on screen-based learning, particularly in cases where learning is purely technology-based without human interaction. They also argue persuasively that CLE is potentially the major disruptor of traditional law schools' core functions, by challenging some of the accepted norms in traditional learning in law, such as a reliance on case law and teaching by way of a formal lecture. As the book is the result of research report prepared by the authors with funding from the National Office of Learning and Teaching, it is based on extensive and thorough research in the area of CLE in Australia. The book also considers the complex issues associated with enhancing law students' public-interest professionalism in an Australian context, and offers practical guidance on how to construct and operate a 'best practice' CLE program for the benefit of various stakeholders, including regulators, law deans, associate deans, law teachers and students.